Specificity of retroviral RNA packaging. - Aronoff, R (1991)
Encapsidation of retroviral RNA has been shown to be dependent on specific cis-acting signals, in particular, the packaging region (psi) located near the 5' end of the retroviral genome. In this report, we show that a 683-base avian extended packaging sequence (psi+) derived from Rous sarcoma virus will direct packaging of heterologous hygromycin mRNA into avian virions when present at the 3' end of the transcript in the sense orientation. However, this packaging is not as efficient as the packaging of RNA encoded by a standard avian retroviral vector. A quail cell line containing a Rous sarcoma virus mutant, SE21Q1b, produces virions which will package endogenous cellular mRNAs randomly, roughly in proportion to their intracellular concentrations. We found that viral particles from SE21Q1b retain the capacity to specifically encapsidate hygromycin mRNAs containing the avian psi+. To determine whether packaging of cellular mRNA would occur in other retroviral packaging lines, we assayed virion RNA isolated from the retroviral particles produced by avian and murine packaging lines for the presence of endogenous cellular mRNAs. Endogenous cellular mRNAs were not found randomly packaged into virions produced by any of the packaging lines examined except SE21Q1b. Some specific sequences, however, were found packaged into avian virions. Endogenous retrovirus-related mink cell focus-inducing murine leukemia virus RNAs and 30S viruslike RNAs were found to be efficiently packaged into murine virions even in the presence of RNAs containing all cis-acting retroviral sequences.